2018
DOI: 10.2147/ijgm.s165947
|View full text |Cite
|
Sign up to set email alerts
|

Role of intravenous iron in the treatment of anemia in patients with gastrointestinal tract tumors undergoing chemotherapy: a single-center, observational study

Abstract: PurposeThe prevalence of anemia ranges between 30% and 90% in cancer patients, affecting the health status, quality of life, and treatment outcome. Therefore, a proper diagnosis and management of anemia is crucial in these patients. Iron deficiency is diagnosed in~32%–60% of the cases. In this observational study, we evaluated the efficacy and safety of intravenous iron (ferric carboxymaltose [FCM], Ferinject®) in the treatment of iron-deficiency anemia in patients with gastrointestinal tumors undergoing palli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…All studies included a comparator arm, except for Bojesen et al [ 28 ], Lima et al [ 29 ] and, Verhaeghe et al [ 30 ] where all patients received IV iron. Of the RCTs, Keeler et al [ 31 ], Keeler et al [ 32 ], and Talboom et al [ 33 ] compared ferric carboxymaltose (FCM) to oral iron, while Laso-Morales et al [ 34 ] compared FCM to iron sucrose (IS), and Ng et al [ 35 ] compared iron isomaltoside to standard of care.…”
Section: Resultsmentioning
confidence: 99%
“…All studies included a comparator arm, except for Bojesen et al [ 28 ], Lima et al [ 29 ] and, Verhaeghe et al [ 30 ] where all patients received IV iron. Of the RCTs, Keeler et al [ 31 ], Keeler et al [ 32 ], and Talboom et al [ 33 ] compared ferric carboxymaltose (FCM) to oral iron, while Laso-Morales et al [ 34 ] compared FCM to iron sucrose (IS), and Ng et al [ 35 ] compared iron isomaltoside to standard of care.…”
Section: Resultsmentioning
confidence: 99%
“…All studies included a comparator arm, except for Bojesen et al [22], Lima et al[23] and, Verhaeghe et al [24] where all patients received IV iron. Of the RCTs, Keeler et al [25] and Keeler et al [26] compared ferric carboxymaltose (FCM) to oral iron, while Laso-Morales et al [27] compared FCM to iron sucrose (IS), and Ng et al [28] compared iron isomaltoside to standard of care.…”
Section: Resultsmentioning
confidence: 99%
“…Bojesen et al [22] reported a mean increase in Hgb of 2.13 g/dL (95% CI: 1.71-2.55 g/dL; p <0.0001) after four weeks in CRC patients who received iron isomaltoside prior to surgery. In addition, Lima et al [23] reported an absolute increase in mean Hgb of 0.9 g/dL (SD 1.3) from baseline to 12-14 weeks ( p =0.001) in CRC patients who received 1000 mg of IV FCM (Ferinject™) every study visit (12-13 weeks) until anemia or ID was corrected. In contrast, Verhaeghe et al reported no significant increase in Hgb in patients with GI malignancies who received at least one dose of IV FCM preoperatively after a four week follow up period [24].…”
Section: Resultsmentioning
confidence: 99%
“…We have introduced our anaemia pathway to the early stages of our patient pathway in order to afford the greatest duration of time for haematopoesis; as a consequence, we have also treated patients who do not ultimately present to the operating theatre. These patients will still benefit from treatment of iron deficiency anaemia 18 20 21. The introduction of POC Hb testing has facilitated diagnosis and treatment of iron deficiency anaemia during a single preassessment clinic attendance.…”
Section: Lessons and Limitationsmentioning
confidence: 99%